2022
DOI: 10.1021/acs.iecr.2c03453
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching and Highly Selective Adsorption of Ag+ Using N-Doped Graphene Quantum Dots/Poly(vinyl alcohol) Composite Membrane

Abstract: Fabrication of composite adsorbents with exceptional fluorescence performance has attracted increasing attention. In this study, a nitrogen-doped graphene quantum dots (NGQDs)/poly(vinyl alcohol) (PVA) composite membrane (NGQDs-PVA) with high adsorption selectivity and fluorescence quenching for Ag + was prepared via simple cross-linking. The SEM characterization showed that the NGQDs were uniformly distributed in PVA, indicating that the material exhibited fluorescence characteristics of quantum dots. C−O, −C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…75 Recent research by Wang et al reported the effective adsorption of heavy metal Ag using NGQD-PVA composites, where nitrogen and oxygen functional groups were introduced. 76 It's worth noting that GQDs can exhibit different electron behaviors when covalently or non-covalently bonded with other substances. Han et al reported that when GQDs chemically adsorbed onto metal oxide films, they demonstrated enhanced donor–acceptor binding strength and approximately double the interfacial electron transfer rate compared with physical adsorption.…”
Section: Properties Of Gqdsmentioning
confidence: 99%
“…75 Recent research by Wang et al reported the effective adsorption of heavy metal Ag using NGQD-PVA composites, where nitrogen and oxygen functional groups were introduced. 76 It's worth noting that GQDs can exhibit different electron behaviors when covalently or non-covalently bonded with other substances. Han et al reported that when GQDs chemically adsorbed onto metal oxide films, they demonstrated enhanced donor–acceptor binding strength and approximately double the interfacial electron transfer rate compared with physical adsorption.…”
Section: Properties Of Gqdsmentioning
confidence: 99%
“…For decades, various fillers have been incorporated into PVA films and their structure-property relationship has been investigated. GQDs have also been used as fillers in PVA matrices and the enhancement of their luminescence properties has been explored [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the SPM data have been significantly related to photoluminescence (PL) emission results, which is of extreme relevance. Although the photoluminescence of GQD fillers within PVA matrices has already garnered significant interest [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], a thorough investigation of the nanostructural modifications occurring at the surface of PVA/GQD nanocomposites is still lacking. Understanding and manipulating the nanostructure of these films is crucial for tailoring their properties, constituting a fundamental step toward harnessing the full potential of these materials for practical use.…”
Section: Introductionmentioning
confidence: 99%